2006
DOI: 10.1186/1476-069x-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupation, smoking, and chronic obstructive respiratory disorders: a cross sectional study in an industrial area of Catalonia, Spain

Abstract: BackgroundFew studies have investigated the independent effects of occupational exposures and smoking on chronic bronchitis and airflow obstruction. We assessed the association between lifetime occupational exposures and airflow obstruction in a cross-sectional survey in an urban-industrial area of Catalonia, Spain.MethodsWe interviewed 576 subjects of both sexes aged 20–70 years (response rate 80%) randomly selected from census rolls, using the ATS questionnaire. Forced spirometry was performed by 497 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
(26 reference statements)
5
20
3
1
Order By: Relevance
“…Smoking is the major risk factor for chronic bronchitis, a conclusion supported by our data as well. Other authors have suggested interactions between smoking and occupational exposures [Jaen, et al 2006, Mannino 2005 but we saw no evidence of this in our data.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking is the major risk factor for chronic bronchitis, a conclusion supported by our data as well. Other authors have suggested interactions between smoking and occupational exposures [Jaen, et al 2006, Mannino 2005 but we saw no evidence of this in our data.…”
Section: Discussioncontrasting
confidence: 99%
“…Estimates of this percentage for the general population range from 0–37%, with a median value of 15% (4). Higher percentages were reported for non-smokers (12–53%)(1620). In a recent analysis, an 8.8% reduction in occupational exposures to dust/gases/fumes would result in an estimated 20% reduction in the prevalence of COPD worldwide (21).…”
Section: Introductionmentioning
confidence: 91%
“…However, the effect of smoking was stronger than that of dust exposure. It has been suggested that the effect of occupational exposures on lung function is proportionally smaller to that of smoking 16) . Apart of that, the interaction between smoking and occupational exposures complicates further the evaluation of their combined effect on lung physiology.…”
Section: Discussionmentioning
confidence: 99%